2003
DOI: 10.1038/sj.bjc.6601474
|View full text |Cite
|
Sign up to set email alerts
|

Polarisation of a T-helper cell immune response by activation of dendritic cells with CpG-containing oligonucleotides: a potential therapeutic regime for bladder cancer immunotherapy

Abstract: Intravesical bacillus Calmette -Guerin (BCG) is a treatment for transitional cell carcinoma (TCC) and carcinoma in situ (cis) of the urinary bladder, but some patients remain refractory. The mechanism of cancer clearance is not known, but T cells are thought to play a contributory role. Tissue dendritic cells (DCs) are known to initiate antigen-specific immune responses following activation of receptors, which recognise molecular patterns on the surface of microorganisms. A family of these receptors, the toll-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
1
23
0
2
Order By: Relevance
“…The method was performed according to the work of Atkins et al [25] and Grauer et al [26] with some modification. Briefly, the femur and tibia were removed from adult C57BL/6 mice and 300 g male Wistar rats (Charles Rivers Laboratories, UK).…”
Section: Limulus Amoebocyte Lysate Assaymentioning
confidence: 99%
“…The method was performed according to the work of Atkins et al [25] and Grauer et al [26] with some modification. Briefly, the femur and tibia were removed from adult C57BL/6 mice and 300 g male Wistar rats (Charles Rivers Laboratories, UK).…”
Section: Limulus Amoebocyte Lysate Assaymentioning
confidence: 99%
“…This is similar to previous reports that ODN-mediated DC activation is crucial for effective tumor elimination in other therapeutic settings. [34][35][36] In light of recent discovery on contributions of PD-1 and PD-L1 interaction to tumor-induced immune tolerance 54,55 and detectable expression of PD-L1 on Renca-HA cells, it will be of great interests and importance to examine whether our observed enhanced antitumor immunity is related to the interruption of the PD-1/PD-L1 pathway or other mechanisms in future studies. Nevertheless, these studies suggested that in the absence of additional maneuvers beyond BMT, early T-cell homeostatic proliferation mediated by BMT could not provide strong enough stimuli to overcome tumorinduced tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Since ligands for TLR, such as CpG-containing ODN, have been demonstrated to be important factors in mediating DC activation and subsequently augmenting T-cell function to overcome tumor-induced tolerance, [34][35][36] we further explored whether inclusion of DC-activating ODN in combination with GM-CSF treatment in HA-BMT mice would further enhance the function of activated HA-specific T cells. Although ODN treatment alone did not impose significant impacts on the number of in vivo derived DCs, ODN in combination with GM-CSF imposed a significant increase in SP-DC number in treated mice (Figure 3a).…”
Section: Engineered Stem Cells To Treat Lung Metastases X Zhang Et Almentioning
confidence: 99%
“…Besides the well-known proinflammatory Incomplete Freund's Adjuvant (IFA) and coadministration of cytokines such as IL-2, 32 IL-12 63 or GM-CSF, 40 the potent immunostimulatory properties of toll-like receptor (TLR) agonists are rapidly becoming apparent. Thus, TLR-4 ligands including monophosphoryl lipid A (MPL), a chemically modified derivative of lipopolisaccharide (LPS) that exhibits similar immune activation potential, but reduced toxicity compared to LPS, 77 alone or in combination with QS21 (saponin), 52 as well as the synthetic lipid A mimetic Ribi 529, an aminoalkyl glucosaminide 4-phosphate, 77 and the TLR-9 agonist CpG-oligonucleotide 78 were shown to enhance antigen-specific immunity by providing activatory signals to DCs. A novel TLR-2 ligand is the outer membrane protein A of gram-negative bacteria, which has been shown to enhance the induction of specific CTL when mixed with peptide vaccines in mice.…”
Section: Vaccination Strategiesmentioning
confidence: 99%